Hypertension Counseling and Blood Pressure Checks in Coastal Community Groups - Arafah, Salmah; Patmawati, Patmawati; Suardi, Suardi; Sumarmi, Sumarmi; Ernawati, Ernawati; Dewiyanti, Dewiyanti; Oktaviana, Dina; Kamriana, Kamriana; Alwi, Alwi (PABBURA : Health Service Journal, 2024)
Hypertension does not yet occupy the main priority scale in health services for the community, especially in coastal areas, even though it is known that the negative impacts it will cause are quite large, such as stroke and coronary heart disease. Several residents in Topejawa Village, Takalar Regency still suffer from hypertension, even with several complications. Due to the very high incidence of hypertension and the danger of complications it causes, it is necessary to provide education about hypertension, including blood tests. The aim of this community service activity is so that residents in Topejawa Village can monitor their health conditions. The method used is in the form of education about hypertension and matters related to hypertension. Before counseling began, participants were given a pre-test, the average pre-test score was 65.7. After counseling and a question and answer session, participants were given a post-test, the average post-test score was 90.7. There was an increase in participantknowledge of around 25% about hypertension. With this outreach, participants will become more aware of matters related to hypertension and can utilize herbal plants that grow around their residence to prevent or treat hypertension.